Identification and Prioritization of Tourism Development Strategies in Shiraz Applying SWOT technique and ANP model - Mohammad Gholami; Mohsen Rastegar; Alamdar Abdellahi; Razieh Mirjafari (جغرافیا و پایداری محیط, 2015)
The present study aims at recognizing and prioritizing tourism development strategies of Shiraz applying SWOT technique and ANP model. This research is a descriptive-analytical one with deductive logic using field and document methods. First of all, SWOT quadruplet factors were gathered through a questionnaire from tourists (sample size 400), citizens (sample size 400) and experts (30 samples) according to the topic of research. In the next step, the strategies, obtained from the analysis, were prioritized by a 5-member group of expert professors in the field of tourism using network analysis (ANP). Moreover, SWOT quadruplet elements and each of their factor were prioritized toward each other. The findings show that SO1, SO2and ST1are considered as the 3 precedence strategies for Shiraz. SO1 strategy makes an increase in tourism resources of high importance at regional, national and international, which is associated with aggressive strategies. SO2 strategy develops appropriate entertainment centers which increases more staying of tourists, especially foreign tourists. It is also associated with aggressive strategies. ST1 strategy increases the funding for the development and management of tourism attractions and tourism development. In addition it is related to the competitive strategies.